The Legal Relationship Between Holding Company and Subsidiary Company in Foreign Direct Investment in Aceh Upstream Oil and Gas Sector - Pramana, Andika Reza; MH, Nurdin (Student Journal of International Law, 2024)
During 1970-1990, Indonesia emerged as one of the world's largest producers of oil and natural gas. Its management required direct foreign investment due to the need for capital, technology, and skilled human resources. Foreign direct investment activities in Indonesia typically involved the establishment of subsidiaries by foreign and Indonesian companies, necessitating legal regulation governing the relationship between subsidiaries and their holding companies. This study aims to analyze the legal correlation between subsidiaries and holding companies in foreign direct investment, the authority and intervention of holding companies in subsidiaries, and the barriers faced by foreign investment in the upstream oil and gas sector in Aceh. Normative juridical analysis was employed throughout the study period, involving analysis of various books, journals, research papers, and relevant legislative regulations. Consistent with the findings, the legal relationship between subsidiaries and holding companies in direct foreign investment in the upstream oil and gas sector in Aceh is not extensively detailed in Law Number 40 of 2007 concerning Limited Liability Companies. Instead, it is determined by the articles of association and cooperation contracts. As majority shareholders, holding companies have the ability to influence decisions concerning the financial, strategic, business, and operational aspects of subsidiaries. However, foreign investments in this sector encounter challenges related to environmental concerns and the complexity of regulations and administration.